The woman who pretended to be who she was : myths of self-imitation - Doniger, Wendy (Oxford University Press, 2005)
Many cultures have myths about self-imitation, stories about people who pretend to be someone else pretending to be them, in effect masquerading as themselves. This great theme, in literature and in life, tells us that people put on masks to discover who they really are under the masks they usually wear, so that the mask reveals rather than conceals the self beneath the self. In this book, noted scholar of Hinduism and mythology Wendy Doniger offers a cross-cultural exploration of the theme of self-impersonation, whose widespread occurrence argues for both its literary power and its human value. The stories she considers range from ancient Indian literature through medieval European courtly literature and Shakespeare to Hollywood and Bollywood. They illuminate a basic human way of negotiating reality, illusion, identity, and authenticity, not to mention memory, amnesia, and the process of aging. Many of them involve marriage and adultery, for tales of sexual betrayal cut to the heart of the crisis of identity. These stories are extreme examples of what we common folk.; In this book, noted scholar of Hinduism and mythology Wen oniger offers a cross-cultural exploration of the theme or us to become travesties of ourselves, particularly as we age and change. We often slip carelessly across the permeable boundary between the un-self-conscious self-indulgence of our most idiosyncratic mannerisms and the conscious attempt to give the people who know us, personally or publicly, the version of ourselves that they expect. Myths of self-imitation open up for us the possibility of multiple selves and the infinite regress of self-discovery. Drawing on a dizzying array of tales-some fact, some fiction-"The Woman Who Pretended to Be Who She Was" is a fascinating and learned trip through centuries of culture, guided by a scholar of incomparable wit and erudition.